miR-125a Induces HER2 Expression and Sensitivity to Trastuzumab in Triple-Negative Breast Cancer Lines - Ninio-Many, Lihi; Hikri, Elad; Burg-Golani, Tamar; Stemmer, Salomon M.; Shalgi, Ruth; Ben-Aharon, Irit (Frontiers in Oncology, 2020)
The EGFR/HER2 signaling network is an effective therapeutic target for HER2-positive cancers, which are known for their aggressive biological course. Evidence indicates that the EGFR/HER2 network plays a role in the aggressive basal-like subtype as well. Here, we studied the potential role of miR-125a-3p as a modulator of the EGFR/HER2 pathway in basal-like breast cancer. Over-expression of miR-125a-3p reduced the migratory capability of MDA-MB-231 cells and led to an increase in the expression of ErbB2 transcript and protein. The induced ErbB2 responded to trastuzumab and underwent internalization and subsequent intra-lysosomal degradation. Trastuzumab treatment further reduced the migratory capability and induced the apoptosis of the cells. An in-vivo mouse model, which supported the in-vitro findings, showed a synergistic effect for miR-125a-3p and trastuzumab. Trastuzumab-treated miR-125a-3p-induced tumors were significantly smaller than control induced tumors. Our findings indicate that, in the basal-like subtype of breast cancer, miR-125a-3p may act as a tumor suppressor. miR-125a-3p induces an increase in the expression of ErbB2 that may render the cells suitable for treatment with anti-HER2 therapies.